Growth Performance of Commercial Broiler Chicken Fed Dried Azolla. - Sharma, Kuber; Sharma, Arun; Sambyal, Madhu Suman; Sunidhi; katoch, Shivani (Indian Journal of Animal Nutrition, 2025)
A study was undertaken to explore the nutritive value of Azolla pinnata as a non-conventional feed ingredient in broiler feeding. The study was conducted for a period of 42 days with 150-day old unsexed Vencobb chicks divided into 5 groups (1 control + 4 treatments) with 3 replicates having 10 chicks in each replicate. The groups were designated as T0, T1, T2, T3 and T4 where in T0 served as standard control group. Group T1, T2, T3 and T4 were fed with dried azolla at 2, 3, 4 and 5 per cent substitution level, respectively. During the starter phase, results of growth trial revealed significantly higher weight gain and feed conversion ratio in T4 and numerically 4.7% higher weight gain during finisher phase. Overall growth performance (0-42 days) of broiler birds exhibited significantly highest weight gain in T4. There was no effect on palatability of feed with 5 % substitution of azolla. Results for the feed intake, feed conversion ratio, proximate analysis of broiler meat, digestibility coefficients of different nutrients and serum mineral analysis exhibited non-significant (P>0.05) difference. It is thus concluded that 5% substitution of dried azolla in broiler commercial feed positively affects the growth performance and has no effect on palatability of feed. Dried azolla has the potential as an unconventional feed ingredient to be included in the broiler ration at 5 per cent level for economizing the cost of production.